Enhancing The Solar Energy Potential in Malaysia Using The Concentrated Photovoltaic (CPV) Technology - Akorede, Mudathir Funsho (2012)
For over one hundred years now, energy and power production have been generated around the world through the burning of fossil fuels.This global over-dependence on fossil fuel resources is very dangerous from two major perspectives: (i) environmental issues as a result of combustion of these fuels, and (ii) future energy security threat due to their limited supplies, rising cost, etc. Given the scenarios, several efforts have been made globally on the application of green technology and renewable energy in the power generation industry. One of the most abundant and promising resources, relative to other types of sustainable energy in Malaysia, is solar energy. To this end, the government has set a target of 1,250 MW of electricity from PV of a total of 3,000 MW projected to be produced from renewable energy by 2020. Currently, a number of hybrid solar stations have being in operation in various parts of the country. However, the output power from each of these power stations is very small, relative to the set target, due to low efficiency. This paper gives a brief overview of the existing solar PV projects in Malaysia and then carries out a study on how the capacity could be significantly enhanced. One major way to achive this objective, as proposed inthis study, is replacement of the existing conventional PV panels with concentrated photovotaic (CPV) technology. This has the potential to increase the output efficiency from 25 % of the conventional PV to more than 40 %.To carry out the investigation, 6 CPV panels have been installed on our project site, from which the power output and other parameters could be collected and analysed accordingly.